2019
DOI: 10.1097/tp.0000000000002450
|View full text |Cite
|
Sign up to set email alerts
|

NKG2C Natural Killer Cells in Bronchoalveolar Lavage Are Associated With Cytomegalovirus Viremia and Poor Outcomes in Lung Allograft Recipients

Abstract: Background: Cytomegalovirus (CMV) infection is a risk factor for chronic lung allograft dysfunction (CLAD), which limits survival in lung allograft recipients. Natural killer (NK) cells that express the NKG2C receptor mediate CMV-specific immune responses. We hypothesized that NKG2C + NK cells responding to CMV in the lung allograft would reduce CMV-related inflammation and would improve CLAD-free survival. Methods: We prospectively followed 130 subjects who underwent lung transplantation from 2012 to 2016. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…Our findings may have broader implications, as NK cells can play multiple important roles in the context of lung transplantation (45). In addition to the effects observed on IRI, NK cells appear to impact CLAD outcomes both through immune surveillance of CMV (46) and depletion of host antigen-presenting cells (47). While NK cell depletion could increase infection or rejection risks, targeting NK-associated receptors most associated with ischemia reperfusion injury, such as NKG2D, could ameliorate this concern.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings may have broader implications, as NK cells can play multiple important roles in the context of lung transplantation (45). In addition to the effects observed on IRI, NK cells appear to impact CLAD outcomes both through immune surveillance of CMV (46) and depletion of host antigen-presenting cells (47). While NK cell depletion could increase infection or rejection risks, targeting NK-associated receptors most associated with ischemia reperfusion injury, such as NKG2D, could ameliorate this concern.…”
Section: Discussionmentioning
confidence: 80%
“…12 gd T cells can also express the receptors from the CD94-NKG2 family, which recognize the non-classical MHC class I molecule human leukocyte antigen (HLA)-E. 13 The upregulation of CD94-NKG2C (NKG2C) on NK cells has been associated with CMV seropositivity, 14 and there are a number of reports describing the contribution of NKG2C+ NK cells in the control of CMV after solid organ and hematopoietic stem-cell transplantation. 15,16 Our own studies 17 and those of others 18 have demonstrated the expansion of NKG2C+ NK cells after CMV replication after LTx, further implicating a role for this receptor in immunity to CMV. However, a role for NKG2C in the context of gd T cells remains largely unexplored.…”
mentioning
confidence: 68%
“…As previously described, most of the memory NK cells were derived from the expansion of adaptive CD57 + NKG2C + cells in a context of cytomegalovirus seropositivity (6, 7). Although NKG2C overexpression has not been demonstrated in lung NK cells from healthy donors (11), it could be hypothesized that, as being the site of many viral infections, the lung would be an interesting tissue in which to study the acquisition of NK cell memory (28).…”
Section: Nk Cells In the Normal Lungmentioning
confidence: 99%